Measuring financial distress in German cancer patients: development and validation of the Financial Distress of Cancer Assessment Tool (FIAT) - Richter, Luise Johanna; Pauge, S.; Mehlis, Katja; Züger, Andrea; Surmann, B.; Mathies, V.; Greiner, W.; Ernst, T.; Winkler, Eva C.; Menold, N. (ESMO open, 2024)
Background - Cancer diagnosis and therapy can lead to significant financial distress for those affected, even in universal health care systems. We present the development and validation of a patient-reported outcome measure for financial distress in German cancer patients. - Methods - Validation of the newly developed instrument followed a two-step approach, including two quantitative paper-pencil surveys (N1 = 111, N2 = 267) with patients of all types of cancer and treatment status at two German university hospitals. Factorial validity, reliability, construct, and criterion validity were assessed using exploratory and confirmatory factor analysis, correlative and linear regression analysis. - Results - The Financial Distress of Cancer Assessment Tool (FIAT) comprises 19 items across three domains of subjective financial distress: (i) financial worries; (ii) dissatisfaction across various life domains, and (iii) challenging experiences with authorities and benefit providers (e.g. employment agency, health insurance). Confirmatory factor analysis confirmed the instrument’s factorial structure. Composite reliability (Raykov’s rho) ranges from 0.88 to 0.96, and retest reliability ranges from 0.64 to 0.75. Correlational analyses showed significant associations between FIAT scores and related constructs [e.g. correlations with the EORTC-QLQ-C30 financial distress subscale (Q28) ranging from 0.47 to 0.60], supporting its construct validity. Additionally, higher FIAT scores were significantly associated with lower health-related quality of life measured by Q29 and Q30 of the EORTC-QLQ-C30, with correlations ranging from −0.21 to −0.28. They were also positively correlated with depression (PHQ-4), with correlations ranging from 0.33 to 0.45, and anxiety (PHQ-4) with correlations ranging from 0.25 to 0.36, confirming its criterion validity. - Conclusions - The newly developed patient-reported outcome measure is the first reported measurement tool to assess financial distress in German cancer patients. The instrument can be used for research purposes and to enable the provision of coordinated support services.
Online verfügbar: 29. November 2024
Gesehen am 03.06.2025